Strategies Used in Teaching Entrepreneurship Component of Economic and Management Sciences in uThukela Education District - Lungelo Sithuthuko Mbatha; Sithembele Goodman Ndovela (E-Journal of Humanities, Arts and Social Sciences)
This research paper reports on findings on strategies teachers used in the teaching of the Entrepreneurship component of Economic and Management Sciences (EMS) in the uThukela district, KwaZulu-Natal, South Africa. Using a qualitative interpretive case study, the researchers purposively recruited and interviewed five EMS teachers from five secondary schools regarding the teaching of the Entrepreneurship component of EMS. Semi-structured interviews were used as a data generation method. The study employed Shulman’s (1986) theory of teacher knowledge to think through and theorise teachers’ strategies for the teaching of the Entrepreneurship component of EMS. The findings revealed that EMS teachers use code-switching in teaching Entrepreneurship, utilise learners’ previous knowledge to introduce new content, use assessment in teaching the Entrepreneurship component, prior knowledge on entrepreneurship to make sense of the subject matter. The study recommends that EMS teachers should consider switching to IsiZulu learners’ home language when they clarify the difficult subject matter of EMS.